2013
DOI: 10.1111/tbed.12118
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus in Wild Boar in the Central Northern Part of Italy

Abstract: Hepatitis E virus (HEV) is responsible for sporadic acute hepatitis in developed countries, where the infection is acquired probably through ingestion of contaminated food, in addition to travel-related cases. In this study, the circulation of HEV in wild boar from nine Italian provinces was evaluated. An overall seroprevalence of 10.2% was found, although there were differences among the provinces, while no samples were positive for HEV RNA detection. This study indicates an active circulation of HEV in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 34 publications
10
50
4
Order By: Relevance
“…Prevalence reported in other European countries vary widely from different countries and within each country: 3 % in the Netherlands (Rutjes et al 2010), 25 % in Portugal (Mesquita et al 2014), 11 and 12.2 % in Hungary (Reuter et al 2009;Forgách et al 2010), 14.9 and 68.2 % in Germany (Adlhoch et al 2009;Schielke et al 2009). Some authors hypothesize that these differences could be attributed to the biology, to different habitats where wild boar populations live and to the different densities of populations in different areas, and to the possibility of contact with pigs in which the infection is widespread (Martelli et al 2008;Martinelli et al 2013). Regarding the sex and age classes of analyzed wild boars, no significant differences were found in agreement with the previous studies (Martelli et al 2008;de Deus et al 2008a;Adlhoch et al 2009;Schielke et al 2009;Martinelli et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence reported in other European countries vary widely from different countries and within each country: 3 % in the Netherlands (Rutjes et al 2010), 25 % in Portugal (Mesquita et al 2014), 11 and 12.2 % in Hungary (Reuter et al 2009;Forgách et al 2010), 14.9 and 68.2 % in Germany (Adlhoch et al 2009;Schielke et al 2009). Some authors hypothesize that these differences could be attributed to the biology, to different habitats where wild boar populations live and to the different densities of populations in different areas, and to the possibility of contact with pigs in which the infection is widespread (Martelli et al 2008;Martinelli et al 2013). Regarding the sex and age classes of analyzed wild boars, no significant differences were found in agreement with the previous studies (Martelli et al 2008;de Deus et al 2008a;Adlhoch et al 2009;Schielke et al 2009;Martinelli et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Coypus are, in fact, a possible food resource for humans, considering that meat from nutria is commonly consumed in South America and in some European countries such as France and Germany (Gło-gowski et al 2010). Taking into consideration the limited amount of data available on HEV prevalence in wild boars in Italy (Martelli et al 2008;Martinelli et al 2013;Caruso et al 2015) and the absence of data on other wild game species, the aim of this study was to investigate the circulation of HEV in the three most hunted wild species in Italy (Sus scrofa, Capreolus capreolus and Lepus europaeus). Moreover, to investigate whether HEV circulates in coypu, we tested liver samples from wild coypu collected during control or eradication programs.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the sample size was performed using the expected prevalence in the selected geographical area (Pisa Province, Tuscany, Italy; Martinelli et al 2013) and the predicted number of free ranging wild boar in the study area (about 6,000 free ranging animals shot per year). The proper sample size to be included in the study was calculated with EpiTools (http://epitools.ausvet.com.au) and resulted in 62 units.…”
Section: Sample Estimationmentioning
confidence: 99%
“…Phylogenetic analysis of 10 positive samples demonstrated that all isolates belonged to genotype 3; however, no subtyping or seroprevalence tests were carried out. In a more recent study, Martinelli et al [15] conducted a serological and virological survey on 2211 wild boar serum and 493 liver samples collected from the central northern areas of Italy during the hunting seasons between 2009 and 2012. The seroprevalence was 10.2 %, no statistically significant association with age was found, and no HEV RNA was detected in either the liver or serum samples.…”
Section: Introductionmentioning
confidence: 99%